Creating target characteristics of wood-plastic composites (WPC) - Drpić Aleksandar D. (Tehnika)
Wood-plastic composites (WPC) represent modern materials with expanding applications. In terms of the quality/cost ratio, WPC has proven to be of exceptional quality on the market compared to other materials of the same or similar purposes. In creating the target characteristics of WPC products, the starting point is the type of components, their interaction and the applied matrix. In this work, the emphasis was on mechanical and physical characteristics, which due to their importance often represent the basis of research. An insight into the current situation is given - the use of WPC products, an overview of selected influences important for the process of creating the target characteristics of WPC, selected modern examples of the creation of target characteristics, as well as an example of a study of the basic physical characteristics of WPC on a group of products (synergy of parameters).